COVID-19 and Tourism in South Asia : Opportunities for Sustainable Regional Outcomes - Twining Ward, Louise; McComb, Jessie F. (World Bank, Washington, DC, 2020)
COVID-19 (coronavirus) is affecting nearly 47.7 million travel and tourism jobs across South Asia, many held by women and vulnerable communities working in the informal sector. Losses of over 50 billion US dollars in gross domestic product in the region are expected in the travel and tourism sector alone as a result of the crisis. Governments are already responding with emergency programs to help small and medium enterprises stay afloat and save jobs. As the South Asia region moves from crisis to recovery planning, governments and destinations have an opportunity to think strategically about the future of their tourism sectors and implement policies that will improve the industry. This regional brief is designed to raise awareness of the importance of tourism to the region and to the World Bank's regional portfolio, highlight some measures being taken by governments and the Bank to address the crisis, and provide recommendations for short- and medium-term sustainable regional recovery, including through greater intraregional tourism. The brief covers Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. Afghanistan was excluded due to a lack of data.